Implementation Process of a Canadian Community‐based Nurse Mentorship Intervention in HIV Care. (May 2016) - Caine, Vera; Mill, Judy; O'Brien, Kelly; Solomon, Patricia; Worthington, Catherine; Dykeman, Margaret; Gahagan, Jacqueline; Maina, Geoffrey; De Padua, Anthony; Arneson, Cheryl; Rogers, Tim; Chaw‐Kant, Jean
Abstract : N/A: We describe salient individual and organizational factors that influenced engagement of registered nurses in a 12‐month clinical mentorship intervention on HIV care in Canada. The intervention included 48 nurses and 8 people living with HIV (PLWH) who were involved in group‐based and one‐on‐one informal mentorship informed by transformative learning theory. We evaluated the process of implementing the mentorship intervention using qualitative content analysis. The inclusion of PLWH as mentors, the opportunities for reciprocal learning, and the long‐term commitment of individual nurses and partner organizations in HIV care were major strengths. Challenges included the need for multiple ethical approvals, the lack of organizational support at some clinical sites, and the time commitment required by participants. We recommend that clinical mentorship interventions in HIV care consider organizational support, adhere to the Greater Involvement of People Living with HIV/AIDS principles, and explore questions of professional obligations.